Sexual behaviours, awareness and perceptions towards voluntary medical male circumcision among students in Dr Kenneth Kaunda District, South Africa - Sam Mndzebele; Lebogang G. Matonyane (AOSIS, 2019)
Background: Voluntary Medical Male Circumcision (VMMC) is regarded as the most cost-effective intervention in reducing female-to-male transmission of HIV in countries where heterosexual transmission is the most prevalent mode of infection. Objectives: The aim of the study was to determine the awareness, sexual behaviours and perceptions of college students in Dr Kenneth Kaunda District, South Africa. Method: A cross-sectional design was engaged among a sample of 400 students selected using a stratified random sampling method. Descriptive data analysis was engaged to analyse data using STATA 13. Results: The mean age of the respondents was 23 years. About 50% of the respondents were below the age of 23 years. The majority among the ethnic groups were black people and or African people (87.5%), followed by people of mixed race (8.1%). Most of the students belonged to the Christian religion (94.7%), and about 91.3% were single, while only 6.0% lived with their partners. Among those who were circumcised, a majority (78.0%) had undergone the MMC. About 76.5% of those residing in urban areas, and 80.6% residing in rural areas were circumcised. About 90.3% of the participants had good awareness about VMMC. About 77.3% of the participants disagreed that VMMC reduces the size of the penis, while 57.0% felt that VMMC provides an individual with the status of being a real man in society. Only 14.3% felt that VMMC exposes the penis to environmental hazards. While almost half (47.7%) of the cohort had one sexual partner, about 20.9% had three or more sexual partners. Conclusion: The findings suggest that there is a high level of awareness on VMMC among college students in relation to its positive role towards reducing STIs and the enhancement of penile hygiene.